Study on the total synthesis of velbanamine: Chemoselective dioxygenation of alkenes with PIFA via a stop-and-flow strategy - Liu, Huili; Zheng, Kuan; Lu, Xiang; Wang, Xiaoxia; Hong, Ran (Beilstein Journal of Organic Chemistry, 2013)
A “stop-and-flow” strategy was developed for the chemoselective dioxygenation of alkenes with a PIFA-initiated cyclization. This method is conceived for the desymmetrization of seco-diene, and a series of substituted 5-hydroxymethyl-γ-lactones were constructed after hydrolysis. This strategy also differentiates terminally substituted alkenes and constitutes a potentially novel synthetic approach for the efficient synthesis toward velbanamine.
Keywords: alkene; desymmetrization; dioxygenation; lactone; PIFA; velbanamine

The Alkaloids - Neuss, N.; Neuss, M. N. (Academic Press, 1990)

(untitled) - Mangeney, P.; Andriamialisoa, R. Z.; Langlois, N.; Langlois, Y.; Potier, P. (J. Am. Chem. Soc., 1979)

(untitled) - Kutney, J. P.; Choi, L. S. L.; Nakano, J.; Tsukamoto, H.; McHugh, M.; Boulet, C. A. (Heterocycles, 1988)

(untitled) - Kuehne, M. E.; Zebovitz, T. C.; Bornmann, W. G.; Marko, I. (J. Org. Chem., 1987)

(untitled) - Kuehne, M. E.; Matson, P. A.; Bornmann, W. G. (J. Org. Chem., 1991)

(untitled) - Bornmann, W. G.; Kuehne, M. E. (J. Org. Chem., 1992)

(untitled) - Magnus, P.; Mendoza, J. S.; Stamford, A.; Ladlow, M.; Willis, P. (J. Am. Chem. Soc., 1992)

(untitled) - Yokoshima, S.; Ueda, T.; Kobayashi, S.; Sato, A.; Kuboyama, T.; Tokuyama, H.; Fukuyama, T. (J. Am. Chem. Soc., 2002)

(untitled) - Kuboyama, T.; Yokoshima, S.; Tokuyama, H.; Fukuyama, T. (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Ishikawa, H.; Colby, D. A.; Boger, D. L. (J. Am. Chem. Soc., 2008)

(untitled) - Ishikawa, H.; Colby, D. A.; Seto, S.; Va, P.; Tam, A.; Kakei, H.; Rayl, T. J.; Hwang, I.; Boger, D. L. (J. Am. Chem. Soc., 2009)
And references cited therein.

(untitled) - Noble, R. L.; Beer, C. T.; Cutts, J. H. (Ann. N. Y. Acad. Sci., 1958)

(untitled) - Noble, R. L. (Lloydia, 1964)

(untitled) - Svoboda, G. H.; Neuss, N.; Gorman, M. (J. Am. Pharm. Assoc., Sci. Ed., 1959)

(untitled) - Neuss, N. (Bull. Soc. Chim. Fr., 1962)

(untitled) - van Beck, T. A.; Verpoorte, R.; Baerheim Svendsen, A. (Tetrahedron, 1984)

(untitled) - Buechi, G.; Kulsa, P.; Rosati, R. L. (J. Am. Chem. Soc., 1968)

(untitled) - Buechi, G.; Kulsa, P.; Ogasawara, K.; Rosati, R. L. (J. Am. Chem. Soc., 1970)

(untitled) - Kutney, J. P.; Bylsma, F. (J. Am. Chem. Soc., 1970)

(untitled) - Narisada, M.; Watanabe, F.; Nagata, W. (Tetrahedron Lett., 1971)

(untitled) - Kutney, J. P.; Bylsma, F. (Helv. Chim. Acta, 1975)

(untitled) - Takano, S.; Hirama, M.; Ogasawara, K. (J. Org. Chem., 1980)

(untitled) - Takano, S.; Yonaga, M.; Chiba, K.; Ogasawara, K. (Tetrahedron Lett., 1980)

(untitled) - Takano, S.; Uchida, W.; Hatakeyama, S.; Ogasawara, K. (Chem. Lett., 1982)

Medicinal Natural Products: A Biogenetic Approach - Dewick, P. M. (John Wiley & Sons, 2001)

(untitled) - Kolb, H. C.; VanNieuwenhze, M. S.; Sharpless, K. B. (Chem. Rev., 1994)
See for a review of osmium in the Upjohn dihydroxylation and Sharpless dihydroxylation.

(untitled) - Fatiadi, A. J. (Synthesis, 1987)
See for a synthetic method with manganese.

(untitled) - Park, C. P.; Lee, J. H.; Yoo, K. S.; Jung, K. W. (Org. Lett., 2010)
See for a synthetic method with palladium.

(untitled) - Wang, A.; Jiang, H.; Chen, H. (J. Am. Chem. Soc., 2009)
See for a synthetic method with palladium.

(untitled) - Li, Y.; Song, D.; Dong, V. M. (J. Am. Chem. Soc., 2008)
See for a synthetic method with palladium.

(untitled) - Zhang, Y.; Sigman, M. S. (J. Am. Chem. Soc., 2007)
See for a synthetic method with palladium.

(untitled) - Plietker, B.; Niggemann, M. (Org. Lett., 2003)
See for a synthetic method with ruthenium.

(untitled) - Göksel, H.; Stark, C. B. W. (Org. Lett., 2006)
See for a synthetic method with ruthenium.

(untitled) - Fujita, M.; Costas, M.; Que, L., Jr (J. Am. Chem. Soc., 2003)
See for a synthetic method with iron.

(untitled) - Oldenburg, P. D.; Shteinman, A. A.; Que, L., Jr (J. Am. Chem. Soc., 2005)
See for a synthetic method with iron.

(untitled) - Prévost, C. (C. R. Hebd. Seances Acad. Sci., 1933)
See for silver in the Prévost–Woodward reaction.

(untitled) - Woodward, R. B.; Brutcher, F. V., Jr (J. Am. Chem. Soc., 1958)
See for silver in the Prévost–Woodward reaction.

(untitled) - Moriarty, R. M.; Vaid, R. K.; Koser, G. F. (Synlett, 1990)
See for early studies hyperiodine chemistry.

(untitled) - Wirth, T. (Angew. Chem., Int. Ed., 2005)
See for a recent perspective.

Advances in Hetreocyclic Natural Products - Knapp, S. (AI Press, 1996)

(untitled) - Robing, S.; Rousseau, G. (Tetrahedron, 1998)

(untitled) - Castellanos, A.; Fletcher, S. P. (Chem.–Eur. J., 2011)

(untitled) - Denmark, S. E.; Kuester, W. E.; Burk, M. T. (Angew. Chem., Int. Ed., 2012)

(untitled) - Schmidt, V. A.; Alexanian, E. J. (Angew. Chem., Int. Ed., 2010)
See for a radical process for aerobic dioxygenation of alkenes.

(untitled) - Fujioka, H.; Ohba, Y.; Hirose, H.; Murai, K.; Kita, Y. (Angew. Chem., Int. Ed., 2005)

(untitled) - Tellitu, I.; Urrejola, A.; Serna, S.; Moreno, I.; Herrero, M. T.; Dominguez, E.; SanMartin, R.; Correa, A. (Eur. J. Org. Chem., 2007)

(untitled) - Clive, D. L. J.; Peng, J.; Fletcher, S. P.; Ziffle, V. E.; Wingert, D. (J. Org. Chem., 2008)

(untitled) - Cossy, J.; Mirguet, O.; Pardo, D. G. (Synlett, 2001)

(untitled) - Wardrop, D. J.; Bowen, E. G.; Forslund, R. E.; Sussman, A. D.; Weerasekera, S. L. (J. Am. Chem. Soc., 2010)
See for mechanistic proposals for the oxyamidation of alkenes.

(untitled) - Lovick, H. M.; Michael, F. E. (J. Am. Chem. Soc., 2010)

(untitled) - Kikugawa, Y. (Heterocycles, 2009)
See for a comprehensive review of nitrenium intermediates.

(untitled) - Mukaiyama, T.; Tamura, Y.; Fujisawa, T. (Bull. Chem. Soc. Jpn., 1964)

(untitled) - Schmir, G. L.; Cunningham, B. A. (J. Am. Chem. Soc., 1965)

(untitled) - Cunningham, B. A.; Schmir, G. L. (J. Am. Chem. Soc., 1966)

(untitled) - Bondar, D.; Liu, J.; Müller, T.; Paquette, L. A. (Org. Lett., 2005)

(untitled) - Hamamoto, H.; Suzuki, Y.; Takahashi, H.; Ikegami, S. (Adv. Synth. Catal., 2007)

(untitled) - Takano, S.; Murakata, C.; Imamura, Y.; Tamura, N.; Ogasawara, K. (Heterocycles, 1981)

(untitled) - Fuji, K.; Node, M.; Naniwa, Y.; Kawabata, T. (Tetrahedron Lett., 1990)

(untitled) - Yokomatsu, T.; Iwasawa, H.; Shibuya, S. (J. Chem. Soc., Chem. Commun., 1992)

(untitled) - Yokomatsu, T.; Iwasawa, H.; Shibuya, S. (Tetrahedron Lett., 1992)

(untitled) - Hart, D. J.; Huang, H. C.; Krishnamurthy, R.; Schwartz, T. (J. Am. Chem. Soc., 1989)

(untitled) - Campell, J. A.; Hart, D. J. (Tetrahedron Lett., 1992)

(untitled) - Trova, M. P.; Wissner, A.; Casscles, W. T., Jr; Hsu, G. C. (Bioorg. Med. Chem. Lett., 1994)

(untitled) - Lu, Z.; Raghavan, S.; Bohn, J.; Charest, M.; Stahlhut, M. W.; Rutkowski, C. A.; Simcoe, A. L.; Olsen, D. B.; Schleif, W. A.; Carella, A.; Gabryelski, L.; Jin, L.; et al. (Bioorg. Med. Chem. Lett., 2003)

(untitled) - Wongsa, N.; Kanokmedhakul, S.; Kanokmedhakul, K. (Phytochemistry, 2011)

(untitled) - Mehellou, Y.; De Clercq, E. (J. Med. Chem., 2010)
See for a recent perspective on anti-HIV drug discovery.

(untitled) - Askin, D. (Curr. Opin. Drug Discovery Dev., 1998)
See for a review.

(untitled) - Cairns, P. M.; Howes, C.; Jenkins, P. R.; Russell, D. R.; Sherry, L. (J. Chem. Soc., Chem. Commun., 1984)

(untitled) - Cairns, P. M.; Howes, C.; Jenkins, P. R. (J. Chem. Soc., Perkin Trans. 1, 1990)